2019
DOI: 10.1007/978-3-030-33226-6_12
|View full text |Cite
|
Sign up to set email alerts
|

CU-Net: Cascaded U-Net with Loss Weighted Sampling for Brain Tumor Segmentation

Abstract: This paper proposes a novel cascaded U-Net for brain tumor segmentation. Inspired by the distinct hierarchical structure of brain tumor, we design a cascaded deep network framework, in which the whole tumor is segmented firstly and then the tumor internal substructures are further segmented. Considering that the increase of the network depth brought by cascade structures leads to a loss of accurate localization information in deeper layers, we construct many skip connections to link features at the same resolu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(21 citation statements)
references
References 11 publications
0
21
0
Order By: Relevance
“…Cascading U‐nets has shown great ability in dense prediction tasks, such as medical image segmentation 27,28 . And in this study, it is firstly applied to dose prediction.…”
Section: Methodsmentioning
confidence: 99%
“…Cascading U‐nets has shown great ability in dense prediction tasks, such as medical image segmentation 27,28 . And in this study, it is firstly applied to dose prediction.…”
Section: Methodsmentioning
confidence: 99%
“…The qualitative segmentation results of different methods are presented in Figure 7, and we can see that fine details could be better recovered by our method. Even though the performance reported here did not represent the state-of-the-art performance on BRATS 2017 [40], it demonstrated that replacing the 3D convolution kernels by the proposed 3D-DSC was able to reduce the risk of overfitting and hence improve the performance via a deeper network.…”
mentioning
confidence: 65%
“…The UNet-LSTM-UNet appends another UNet as an additional image pre-processing step before each slice is fed into the LSTM-UNet. This design, inspired by cascading architectures for brain tumor segmentation [36], similarly allows for variable slice number volumes, 3D-2D segmentation, and provides increased numbers of trainable convolutions and parameters earlier within the architecture, potentially allowing for improved labeling of vessels within each slice.…”
Section: Nested Model Architecturesmentioning
confidence: 99%